The Interdependence between Parental Emotion Regulation and Children\'s Socialization of Emotions - H. Kazemi Askarani; P. S. Seyedmousavi, Ph.D. (خانواده و پژوهش, 2022)
This study was undertaken to investigate the interdependence between parental emotion regulation and children's socialization of emotions. The present study had a correlational design. The statistical population of this study comprised mothers and fathers of children aged 6-10 studying at primary schools in Tehran in 2018-19 school year from among whom 120 couples were selected using convenience sampling method. The research instruments included Coping with Children's Negative Emotions Scale (CCNES) (Fabes et al., 1990) and Difficulties in Emotion Regulation Scale (DERS) (Gratz & Roemer, 2004). The collected data were analyzed via Pearson correlation method and actor and partner effects using APIM software. The results showed that the actor effect for predicting mothers' supportive and non-supportive reactions to children's emotional reactions through the mothers' difficulty in emotion regulation was not statistically significant (P>0.05). The actor effect for predicting fathers’ supportive and non-supportive reactions to the emotional reactions of children through the father's difficulty in emotion regulation was statistically significant. This means that the father's difficulty in emotion regulation is able to predict fathers' supportive and non-supportive reactions to their children's emotions. However, the partner effects for father's  and mothers' emotion regulation difficulties in predicting father's supportive and non-supportive reactions to the emotional reactions of children were not statistically significant (P>0.05). Hence, it can be stated that parents’ emotion regulation skills have different effects on their supportive and non-supportive reactions to their children's emotions. Furthermore, mothers' difficulty in emotion regulation does not affect the parent-child relationship and their maternal role.